Ancient epistemology - Gerson, Lloyd P. (Key themes in ancient philosophy, 2009)
Ancient and modern perspectives -- The origin of epistemology -- Plato -- Republic -- Theaetetus -- Knowledge versus belief -- Aristotle -- Posterior analytics -- De anima -- Epicureanism and stoicism -- Epicurean epistemology -- Stoic epistemology -- Skepticism -- Pyrrho and the beginning of skepticism -- Academic skepticism -- The pyrrhonist revival -- Plotinus and the neoplatonic synthesis -- The platonist's response to the pyrrhonist -- Knowledge and consciousness -- Imagination -- Varieties of naturalism -- Naturalism redivivus -- Epistemology and nature -- Naturalism and the mental -- Concluding remarks